2015
DOI: 10.1115/1.4029980
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Contributions From Collateral Ligaments to Overall Knee Joint Constraint: An Experimental Cadaveric Study

Abstract: Understanding the contribution of the soft-tissues to total joint constraint (TJC) is important for predicting joint kinematics, developing surgical procedures, and increasing accuracy of computational models. Previous studies on the collateral ligaments have focused on quantifying strain and tension properties under discrete loads or kinematic paths; however, there has been little work to quantify collateral ligament contribution over a broad range of applied loads and range of motion (ROM) in passive constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Previous studies have suggested the possibility of mid‐flexion laxity even after flexion–extension and medial–lateral gap balancing in TKA due to the following mechanism [6, 7]. Although collateral ligaments are tightest at extension, as the knee starts to flex, the distance between the attachment sites of the collateral ligaments becomes smaller, reducing the force applied by these ligaments on the knee joint [7]. In addition, reduction in not only the collateral ligament load, but also the posterior capsular tension and home screw effect, can cause knee laxity to increase up to 30° of flexion [6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the possibility of mid‐flexion laxity even after flexion–extension and medial–lateral gap balancing in TKA due to the following mechanism [6, 7]. Although collateral ligaments are tightest at extension, as the knee starts to flex, the distance between the attachment sites of the collateral ligaments becomes smaller, reducing the force applied by these ligaments on the knee joint [7]. In addition, reduction in not only the collateral ligament load, but also the posterior capsular tension and home screw effect, can cause knee laxity to increase up to 30° of flexion [6].…”
Section: Discussionmentioning
confidence: 99%
“…For varus-valgus rotation, all models behaved almost identically. This was due to the fact that all models had the same ligament prestrain and stiffness, and ligaments have been suggested to have a significant role in varus-valgus rotation 64 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the MCL was a major resistor against valgus rotation and was also actively engaged during external rotation [13,15,16,30,32,33]. The MCL also engaged to a lesser degree during internal rotation [30].…”
Section: Discussionmentioning
confidence: 99%
“…An effective method for measuring the timing and extent of ligament recruitment during knee motion in various degrees-offreedom (DOF) is with experimental tests of knee laxity. Quantitative knee laxity (i.e., knee envelope) tests can provide important information about ligament engagement and overall contributions to knee stability [12][13][14][15][16]. When developing a computational model, knee laxity tests in multiple DOF can be used to calibrate simulated ligament material properties and ensure accurate prediction of ligament-constrained knee motion and loading.…”
Section: Introductionmentioning
confidence: 99%